Long-term deformation measurements of atypical roof timber structures - Bureš, Jiří; Švábenský, Otakar; Kalina, Marek (FCE CTU Prague, 2014)
The paper includes conclusions from evaluation of results obtained from long-term measuring of innovative atypical roof timber structures. Based on the results of measurements of vertical and horizontal deformation components it is possible to analyze the real behaviour of structures in given conditions. By assessing deformations in various stages, including particularly external and internal environment temperatures, relative air humidity and moisture content of wood, decisive parameters for real structure behaviour can be established. The data are processed from period 2001 – 2013.

The paper includes conclusions from evaluation of results obtained from long-term measuring of innovative atypical roof timber structures. Based on the results of measurements of vertical and horizontal deformation components it is possible to analyze the real behaviour of structures in given conditions. By assessing deformations in various stages, including particularly external and internal environment temperatures, relative air humidity and moisture content of wood, decisive parameters for real structure behaviour can be established. The data are processed from period 2001 – 2013.
Long-term deformation measurements of atypical roof timber structures
Keywords: geodetic deformation measurement; atypical roof timber constructions; geodetic deformation measurement; atypical roof timber constructions